2017
DOI: 10.1002/2017je005256
|View full text |Cite
|
Sign up to set email alerts
|

Double jeopardy in astronomy and planetary science: Women of color face greater risks of gendered and racial harassment

Abstract: Women generally, and women of color specifically, have reported hostile workplace experiences in astronomy and related fields for some time. However, little is known of the extent to which individuals in these disciplines experience inappropriate remarks, harassment, and assault. We hypothesized that the multiple marginality of women of color would mean that they would experience a higher frequency of inappropriate remarks, harassment, and assault in the astronomical and planetary science workplace. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 58 publications
2
163
0
Order By: Relevance
“…Women's use of remote sensing and data analysis contributions are notably lower proportionally than men's, whereas participation in fieldwork-based research by people of colour is significantly lower than that of white presenters. This may in part reflect differences in interest, but much research has shown that differential access to research resources and inherent biases and cultural norms (producing a chilly climate) are often also responsible for pushing people to opt out of a scientific field (see Holmes 2015b; Cheryan et al 2017;Clancy et al 2017). By characterising the division of scientific labour in geoscience, scientists and administrators can ask why such differences exist in key areas and make efforts to remedy any such factors in operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Women's use of remote sensing and data analysis contributions are notably lower proportionally than men's, whereas participation in fieldwork-based research by people of colour is significantly lower than that of white presenters. This may in part reflect differences in interest, but much research has shown that differential access to research resources and inherent biases and cultural norms (producing a chilly climate) are often also responsible for pushing people to opt out of a scientific field (see Holmes 2015b; Cheryan et al 2017;Clancy et al 2017). By characterising the division of scientific labour in geoscience, scientists and administrators can ask why such differences exist in key areas and make efforts to remedy any such factors in operation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that people of colour, in particular women of colour, were poorly represented at this conference, just as they are in STEM in the US (Williams et al 2014). Data are not available to compare these proportions to other geoscience conferences; however, the geosciences have the lowest ethnic diversity of any STEM discipline (Huntoon and Lane 2007;Williams et al 2014;Clancy et al 2017). more pronounced than those of gender.…”
Section: Who Presented Where? the Demographics Of The Presentersmentioning
confidence: 99%
See 2 more Smart Citations
“…Although civil rights laws and other government regulations were enacted to make explicit discrimination less likely, some regulations have recently have been weakened, and a rash of sexual harassment revelations have shaken the sciences and public (e.g., Clancy et al 2014Clancy et al , 2017. Informal practices of discrimination persist and discourage women, including women of color, from pursuing advanced education and careers in STEM fields (Gokhale et al 2014).…”
Section: Sociocultural Explanationsmentioning
confidence: 99%